Proposals for an Islamic art program: (A case study) - Faculty of Arts & Media University of Tripoli, Libya / Salaheddin Mansur S. Zagruna - S. Zagruna, Salaheddin Mansur (Institute of Graduate Studies, UiTM, 2018)
After being colonized by the Italian rule for nearly five decades from the early 19th century, Libya underwent a westernization process in all aspects including the areas of art and culture. For instance, the teaching of Arts at the Faculty of Fine Arts (FAM), University of Tripoli, has been adopted a case study for this research. Western perspective in art teaching is not only foreign to Libyan Muslim students, but also incompatible with the Faculty of Arts and Media (FAM) educational philosophy, as well as the philosophy of the Libyan Muslim life and community. These shortcomings have resulted in many conflicts specifically on the moral-ethical values affecting the psychic and spirit of the Muslim art students. Thus, the main aim of this study is to propose a curriculum for teaching Islamic traditional Arts. Such a perspective is deemed relevant to the Muslim students who are taught Islam as addin- away life, is compatible with our belief system in which art and everyday practices (life) are mutually integrated (Tawhid). Such proposals are made possible by examining the philosophy of Islamic art form, content and its underlying aesthetic principles as maintained by Muslim scholars. Also unfolding the Islamic principles in education and as well as unraveling curriculum theory and instructions from renowned scholars’ writings in these fields…